Rethinking inclusive city development amid COVID-19: the Indonesia context - Giska Raissa; Filia Christy; Sandhy Sihotang; Karen Wijaya (The Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Currently, cities all over the world are experiencing pressures caused by the COVID-19 pandemic, including cities in Indonesia. Studies show that the number of poor has been increasing since the spread of COVID-19, mostly in urban areas. Recent news indicates that the pandemic has the potential to add millions of new urban poor due to the threat of future layoffs faced by low-income people. The current condition in Indonesia’s urban areas indicates exclusion of the urban poor, which underlines the need for inclusive city development. Indeed, this crisis exposes the exclusion of vulnerable people, reveals deep inequalities in society and exacerbates the existing inequality among the Indonesian population. Because of the ongoing disruptions that arise in urban areas, the COVID-19 pandemic offers the opportunity to rethink the importance of inclusive city development so that they may become thriving cities for all. Besides, this study also argues that only inclusive cities can grow and thrive under all circumstances and future challenges. This paper discusses how to transform challenges amid COVID-19 to opportunities that can promote inclusive city development. Abstrak. Saat ini, kota-kota di seluruh dunia sedang mengalami tekanan akibat pandemi COVID-19, termasuk kota-kota di Indonesia. Studi menunjukkan bahwa jumlah penduduk miskin terus meningkat sejak penyebaran COVID-19 yang umumnya terjadi di wilayah perkotaan. Berita terbaru menunjukkan bahwa pandemi berpotensi menambah jutaan orang miskin baru di perkotaan akibat ancaman PHK di masa depan yang dihadapi oleh masyarakat berpenghasilan rendah. Kondisi perkotaan di Indonesia saat ini menunjukkan eksklusi dari kaum miskin kota, yang menggarisbawahi perlunya pembangunan kota yang inklusif. Memang, krisis ini mengekspos pengucilan orang-orang yang rentan, mengungkapkan ketidaksetaraan yang dalam di masyarakat dan memperburuk ketimpangan yang ada di antara penduduk Indonesia. Karena gangguan yang terus menerus muncul di perkotaan, pandemi COVID-19 menawarkan kesempatan untuk memikirkan kembali pentingnya pembangunan kota yang inklusif sehingga dapat menjadi kota yang berkembang untuk semua. Selain itu, studi ini juga berkesimpulan bahwa hanya kota inklusif yang dapat tumbuh dan berkembang dalam segala situasi dan tantangan di masa depan. Makalah ini membahas bagaimana mengubah tantangan di tengah COVID-19 menjadi peluang yang dapat mendorong pembangunan kota yang inklusif. Kata kunci. kota inklusif, pengembangan kota, COVID-19, Indonesia.